Educação a céu aberto e escolarização no territorio do formoso: um estudo etnografico a apartir dos saberes e conhecimentos tradicionais locais como contribuição para as escolas estabelecidas nas comunidades quilombolas OlhoD’ água e Lagoa Mirim - Aires, Geovania Machado (2016)
In this work, the idea of an "open education" is precisely what we experience in the territory, along the process of transmitting traditional knowledge and knowledge. These knowledges and knowledge are not mentioned in the curriculum plans of schooling, although Law 9.394 of 1996 notes the need for dialogue between rural schools and place knowledge, and although several treaties to which Brazil is a signatory value the material and non-material patrimony of Traditional knowledge and require "consultation" for the implementation of any project in the communities. However, interaction with the place identities does not occur in the schools investigated, Cosme Almur Dequeixes and Tomaz de Aquino Souza, located in the Water eye and Lagoon Mud communities. The open education that we live in and that we research here, tries to value the knowledge and makes us question what are the learning needs in that territory, precisely so that we can develop practices of interchange with the school space. We can also observe how rich is the territory that practices its numerous knowledge and puts in circulation so much information for the social and culture reproduction of the social groups that live there, in the Territory of Handsome. An education that is present daily through the countryside, the making of the flour, the ritual of healing, the culture practices performed, whether in festive or holiness movement, of the medicinal herbs used by pharmacists, doctors of the bush, midwives and healers, and Meetings and meetings held in these Quilombola communities. A schooling that contemplates the already open education perspective can even help to face the conflicts imposed on the community. Many conflicts experienced could be used as didactic content in material already produced, including by other researchers of the New Social Cartography Project, which deals with the installation of large projects, deforestation and burning of the areas of babassu, sale of land and illegal wood, Threats and deaths, pollution of natural fields and electric fences in standing forest area. These are subjects that could be explored in the quilombolas schools of the Territory of Handsome. This work is part of an attempt to establish a dialogue between my belonging as a researcher and my membership as a quilombola in relation to the perception of the educational processes practiced in the two communities mentioned in the Territory of Handsome, Downloaded, Maranhão.